The Radiography and Ultrasonography in the Diagnosis and Monitoring of Necrotizing Enterocolitis in Neonates: A Focused Review - Majchrzycka, Marta; Czapla, Natalia; Graczyk , Martyna; Graczyk , Natalia; Ignyś, Piotr; Łopińska, Joanna; Majchrzak, Mateusz; Strużyńska, Ewelina; Wisoky, Wiktor; Ziółkowska, Weronika (Quality in Sport, 2026)
Necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease that predominantly affects preterm neonates and remains a major source of morbidity and mortality in neonatal intensive care units (NICUs). An early diagnosis and timely surveillance is key to optimizing the outcome of the patients. Abdominal X ray (X Ray) remains the cornerstone of the imaging of NEC with pneumatosis intestinalis, portal venous gas and pneumoperitoneum being well defined radiological signs. With the increasing role of ultrasonography (USG) in the management of NEC, the bedside evaluation of bowel thickness, vascularity, motility and the assessment of fluid collections can sometimes detect signs of NEC before they become evident on radiography. This review summarizes the role of radiography and ultrasonography in the imaging of NEC, highlights their respective merits and shortcomings, and describes the practical approaches for their use in clinical practice. It also discusses the role of contrast enhanced ultrasound, near-infrared spectroscopy and artificial intelligence in the imaging of NEC.